Square-Wave Stripping Voltammetric Analysis of Human Papilloma Virus 58 DNA on Carbon Fiber Microelectrode - LY, SUW-YOUNG; JUNG, WOON-WON; KIM, SUNG-KUK; KIM, MYUNG-HOON (Asian Journal of Chemistry, 2010)
Electrochemical behaviour of polymerase chain reaction (PCR) products of human papilloma virus (HPV) 58 DNA was studied employing cyclic voltammetry (CV) and square-wave stripping voltammetry (SWSV) on a carbon fiber micro-electrode (CFME) in order to develop a simple electroanalytical method to detect and determine HPV 58. This is to seek a possible substitute method for the common technique of gel electrophoresis and fluorescent image analysis for its detection. An anodic stripping peak that appears at -0.6 V (versus Ag/AgCl) was utilized for the determination. Optimum conditions for the square-wave adsorptive stripping analysis were found to be -1.0 V of deposition potential, 90 s of deposition time, 150 mV of SW amplitude, 4 mV of step potential and 120 Hz of SW frequency. A linear curve was obtained in a concentration range of 0.01-0.23 mg/L. The relative standard deviations at 0.01, 0.05 and 0.09 mg/L of concentration were 3.1, 2.7 and 5.3 % (n = 5), respectively at the optimum conditions. The detection limit (S/N) was found to be 0.006 mg/L. The method was applied to determine HPV 58 DNA from a real sample from a patient infected for the diagnostic purpose.